Analisis Yuridis Syar’i Terhadap Praktik Khitbah dan Problematika Hukum Keluarga Islam di Indonesia - Nuraziza, Fanisa; Damaiyanti, Dini Stevani; Salma, Rihadatul Aisya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Marriage is a sacred bond carrying significant legal, social, and theological implications in Indonesia. Prior to the solemnization of the marriage contract, Islamic law recognizes a preparatory phase known as *khitbah* (betrothal), serving as a means of *ta’aruf* (mutual acquaintance) to assess compatibility between prospective partners. However, the dynamics of modernity have triggered a shift in values, leading to issues such as the transgression of Sharia boundaries following the betrothal, the practice of covert unregistered marriages (*nikah siri*), and a high incidence of unilateral cancellations that cause both material and psychological harm. This qualitative study, utilizing a literature review method, aims to analyze the legal boundaries of Sharia ethics and identify solutions to various Islamic family law issues regarding the practice of *khitbah* in Indonesia. The analysis reveals that the status of *khitbah* does not render the relationship *halal* (permissible) prior to the actual marriage contract. Regarding detrimental unilateral cancellations, Article 13 paragraph (3) of the Compilation of Islamic Law (KHI) and civil law mechanisms—specifically lawsuits based on Unlawful Acts (*Perbuatan Melawan Hukum* or PMH)—can serve as solutions for the restitution of the victim’s material rights.